Tracking changes in the land use, management and drainage status of organic soils as indicators of the effectiveness of mitigation strategies for climate change. (January 2017) - Untenecker, Johanna; Tiemeyer, Bärbel; Freibauer, Annette; Laggner, Andreas; Luterbacher, Jürg
Abstract: The tracking of land use since 1990 presents a major challenge in greenhouse gas (GHG) reporting under the United Nations Framework Convention on Climate Change (UNFCCC) and the Kyoto Protocol because there is often limited availability of data, especially for the base year of 1990. There is even less land management and soil moisture data, which are needed to track climate change mitigation activities since soil moisture is one of the main drivers of GHG emissions of organic soils. Information is also needed for the reporting of land-based activities such as grazing land management or wetland drainage and rewetting of organic soils. Different spatial and thematic resolutions of land-use data produce inconsistent time series with a strong overestimation of land-use change (LUC) if not adequately accounted for. Our aim was to create a consistent time series of land use since 1990 that is in line with GHG reporting under the UNFCCC and the Kyoto Protocol by combining official cadastral data with colour-infrared aerial photography used for biodiversity monitoring in six federal states in northern and eastern Germany. We developed a generic hierarchical classification by land use, management and drainage status, and a translation key for data harmonisation into a consistent time series. This time series enabled the quantification of LUC on organic soils between 1992 and 2013 in a spatially explicit manner. Furthermore we used this time series to develop indicators for changes in land management and drainage to evaluate the success of protection statuses on peatland restoration. The study area encompassed one million hectares, half of which had some type of legal nature protection status. Areas with no protection status tended to become more intensively farmed and drier, while highly protected areas ( e.g. Natura 2000) showed the opposite trend. Land-use trends also differed greatly between federal states. In Schleswig-Holstein organic soils tended to become drier during the study period, while in Mecklenburg-Western Pomerania they tended to become wetter overall. The trends and differences in LUC between federal states were linked to German reunification, changes in the European Common Agricultural Policy (CAP) and Germany's Renewable Energy Act (EEG). A large-scale peatland protection programme also had major impact. In conclusion, our study demonstrates how data derived for biodiversity monitoring and other highly detailed land-use data can be used to track changes in land use, management and drainage status in accordance with the reporting requirements under the UNFCCC and the Kyoto Protocol.